Pengaruh Penerapan Teknologi Dan Kelembagaan Pertanian Terhadap Peran Petani Champion Serta Keberhasilan Usahatani Cabai Merah (Capsicum annuum, L) (Suatu Kasus di Kecamatan Pacet, Kabupaten Cianjur, Jawa barat) - Albi Rohsan; Euis Dasipah (OrchidAgri, 2023)
This study aims to determine the factors that influence the success of big red chili farming. In this case is the application of technology, the role of agricultural institutions, the role of champion farmers. The method used is a survey of red chili farmers. Respondents were taken by census with a size of 68 units. The analysis technique used is path analysis with two paths. There is a correlation between the Application of Big Red Chili Farming Technology and Agricultural Institutions as indicated by the Pearson correlation coefficient r = 0.693. There is an influence of Agricultural Technology and Institutional Application on the Role of Champion Farmers in Big Red Chili Farming with a total effect of 80.77%. The contribution of each variable is 66.27% and 14.50%. There is an influence of the application of technology, agricultural institutions, and the role of champion farmers on the success of big red chili farming with a total effect of 69.90%. The contribution of each variable is 33.05%; 5.49% and 31.35%.